2015
DOI: 10.3201/eid2101.140640
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcusequisubsp.zooepidemicusInfections Associated with Guinea Pigs

Abstract: Streptococcus equi subsp. zooepidemicus is a known zoonotic pathogen. In this public health investigation conducted in Virginia, USA, in 2013, we identified a probable family cluster of S. zooepidemicus cases linked epidemiologically and genetically to infected guinea pigs. S. zooepidemicus infections should be considered in patients who have severe clinical illness and report guinea pig exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 9 publications
(8 reference statements)
0
29
0
3
Order By: Relevance
“…associated with zoonosis include S. canis, S. zooepidemicus, and S. suis (Fulde and Valentin-Weigand, 2013) (Fig. S. zooepidemicus has been recently transmitted from guinea pigs to their owners, resulting in clinical septicemia (Gruszynski et al, 2015). S. zooepidemicus has been recently transmitted from guinea pigs to their owners, resulting in clinical septicemia (Gruszynski et al, 2015).…”
Section: Diagnosis and Controlmentioning
confidence: 99%
“…associated with zoonosis include S. canis, S. zooepidemicus, and S. suis (Fulde and Valentin-Weigand, 2013) (Fig. S. zooepidemicus has been recently transmitted from guinea pigs to their owners, resulting in clinical septicemia (Gruszynski et al, 2015). S. zooepidemicus has been recently transmitted from guinea pigs to their owners, resulting in clinical septicemia (Gruszynski et al, 2015).…”
Section: Diagnosis and Controlmentioning
confidence: 99%
“…Research has documented a variety of zoonotic disease risks associated with guinea pigs raised under different contexts (Lutz-Wohlgroth et al, 2006;Amman et al, 2007;Fredriksson-Ahomaa, 2007;Walther et al, 2012;Gruszynski et al, 2015). Studies among laboratory research animals have found guinea pigs to carry Campylobacter spp.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the eight outbreak isolates were clustered together with the Chinese strain (ATCC 36246), which caused outbreaks of high mortality in 1975 ( 15 ). In addition, three isolates from human cases with guinea pig exposure (NVSLVA-S19, NVSLVA-S2, and NVSLVA-S22) ( 6 ) were also closely related to the outbreak isolates. In contrast, another swine isolate (AZ-45470), which did not cause a high mortality event, was distant to the outbreak isolates.…”
Section: Resultsmentioning
confidence: 97%
“…Our results showed that the eight outbreak isolates of S. zooepidemicus in this study were classified as ST194, an ST type recorded in the S. zooepidemicus database from two human blood isolates recovered during 2001. Based on the whole genome phylogeny, the eight isolates were also closely clustered with three isolates from human patients who had severe clinical illness with guinea pig exposure ( 6 ), and moreover, their genomic islands and virulence genes were very similar. These results highlight significant public health concerns with these recent United States outbreak isolates.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation